Pengaruh Perlakuan Panas terhadap Sifat Magnetik, Permitivitas dan Permukaan Komposit Ba(2-x)La(x)Fe2O5 ( x = 0,3 dan 0,5 ) - Patricius Purwanto; Ade Mulyawan; Yosef Sarwanto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
Composite of Ba(2-x)La(x)Fe2O5 has been made by powder metallurgy techniques. Ba(2-x)La(x)Fe2O5 were made with mixing of BaCO3, La2O3 and Fe2O3 with a specific weight ratio. The materials composite tobe made with the technique of powder metallurgy with milling method for 2 hours and heat treatment at 800 °C, 900 °C and 1000 °C for 5 hours. After the heat treatment tobe done characterization with using Scanning Electron Microcope ( SEM ) to observe the surface morphology and magnetic properties with Vibrating Sample Magnetometer (VSM) to study the magnetic properties. The composite of Ba(2-x)La(x)Fe2O5 show that the magnetic moment and the magnetic field strength decrease with increasing temperature sintering. Permittivity of Ba(2-x)La(x)Fe2O5 relatif stable af frequence 1 Hz to 100 kHz. The results of surface morphology is known that the morphology of the granulars of composite Ba(2-x)La(x)Fe2O5, regular grains with increasing temperature of sintering, the spectrum EDS (Energy Dispersive Spectroscopy) showed some dominant element indicate that is have same phase of analysis and formation composite magnetic. The composite of Ba(2-x)La(x)Fe2O5 show that the magnetic moment and the magnetic field strength decrease with increasing temperature sintering Keywords: Composite Ba(2-x)La(x)Fe2O5, magnetic, pearmitivity, surface.